Functional insights into Mycobacterium tuberculosis DevR-dependent transcriptional machinery utilizing Escherichia coli. Issue 16 (27th August 2021) - Sharma, Saurabh; Kumar, Ramesh; Jain, Ayushi; Kumar, Manoj; Gauttam, Rahul; Banerjee, Rajdeep; Mukhopadhyay, Jayanta; Tyagi, Jaya Sivaswami
Abstract : DevR/DosR response regulator is believed to participate in virulence, dormancy adaptation and antibiotic tolerance mechanisms of Mycobacterium tuberculosis by regulating the expression of the dormancy regulon. We have previously shown that the interaction of DevR with RNA polymerase is essential for the expression of DevR-regulated genes. Here, we developed a M. tuberculosis -specific in vivo transcription system to enrich our understanding of DevR–RNA polymerase interaction. This in vivo assay involves co-transforming E. coli with two plasmids that express α, β, β′ and σ A subunits of M. tuberculosis RNA polymerase and a third plasmid that harbors a DevR expression cassette and a GFP reporter gene under the DevR-regulated fdxA promoter. We show that DevR-dependent transcription is sponsored exclusively by M. tuberculosis RNA polymerase and regulated by α and σ A subunits of M. tuberculosis RNA polymerase. Using this E. coli triple plasmid system to express mutant variants of M. tuberculosis RNA polymerase, we identified E280 residue in C-terminal domain of α and K513 and R515 residues of σ A to participate in DevR-dependent transcription. In silico modeling of a ternary complex of DevR, σ A domain 4 and fdxA promoter suggest an interaction of Q505, R515 and K513 residues of σ A with E178 and D172 residues of DevR and E471 of σ A, respectively. These findings provide us with new insights into the interactions between DevR and RNA polymerase of M. tuberculosis which can be targeted for intercepting DevR function. Finally, we demonstrate the utility of this system for screening of anti-DevR compounds.